Pengaruh Kualitas Produk terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Konsumen Hanasui di Toko Citra Cosmetic Boulevard - Arnita Nuranita Mudir; Muhammad Ichwan Musa; Muhammad Ilham Wardhana Haeruddin; Isma Azis Riu; Nurul Fadilah Aswar (CV. Lafadz Jaya, 2026)
Indonesia in 1997-1998. The main factor that caused the crisis was the government's widening of the economy, in which the government made concessions to borrow debt without strict supervision and selection. As a result, many businessmen were unable to pay their debts on time, so that Indonesia's reputation declined internationally. Islamic ethics is a branch of philosophy that is critical and rational which investigates good and bad and human obligations. Islam as a comprehensive and universal religion regulates all aspects of human life including in the field of trade or commerce business. In the field of worship, Islam stipulates the law